Development, feasibility and usability of an app for the correct nutrition of children and adolescents with acute lymphoblastic leukemia - Zibaldo, Andrea; Stellato, Pio; Sepe, Gaia; Fenicia, Diana; Scognamiglio, Armando; Zibaldo, Francesco; Parasole, Rosanna; Menna, Giuseppe (Frontiers in Oncology, 2025)
IntroductionProper nutrition during cancer treatment is crucial for children and adolescents with acute lymphoblastic leukemia (ALL), as malnutrition can impact treatment tolerance, survival, and quality of life. In ALL specifically, malnutrition at diagnosis has been associated with increased risk of infections, treatment delays, and poorer survival, while maintaining adequate nutritional status can improve treatment tolerance and long-term outcomes.Materials and methodsWe developed and tested the “Hematognam” app, which provides caregivers with dietary guidance for children and adolescents undergoing chemotherapy. This study evaluates the app’s feasibility and usability among families of children and adolescents with ALL over a three-month period.ResultsThe app received high satisfaction ratings, which suggests its user-centric design and relevance in managing complex dietary challenges associated with treatment.DiscussionThese results align with previous studies demonstrating the potential of digital health tools to enhance treatment compliance and overall well-being in vulnerable populations. By addressing key nutritional challenges faced by children and adolescents with ALL - such as appetite loss, food aversions, gastrointestinal side effects, and food safety concerns - the "Hematognam" app offers a complementary tool to existing dietary counseling, supporting both families and clinicians in daily nutritional management. The development and implementation of the “Hematognam” app proved feasible and effective in addressing the nutritional needs of children and adolescents with ALL during chemotherapy.